2006
DOI: 10.1002/hyp.6185
|View full text |Cite
|
Sign up to set email alerts
|

Effects of surface characteristics on infiltration patterns in an arid shrub desert

Abstract: Abstract:Precipitation is often the sole source of water replenishment in arid and semi-arid areas and, thus, plays a pertinent role in sustaining desert ecosystems. Revegetation over 40 years using mainly Artemisia ordosica and Caragana korshinskii at Shapotou Desert Experimental Research Station near Lanzhou, China, has established a dwarf-shrub and microbiotic soil crust cover on the stabilized sand dunes. The redistribution of infiltrated moisture through percolation, root extraction, and evapotranspiratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
85
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 102 publications
(88 citation statements)
references
References 22 publications
3
85
0
Order By: Relevance
“…The saturated hydraulic conductivity rate and the unsaturated hydraulic conductivity rate near saturation (soil water potential >−0.01 MPa) of the surface soils covered by BSCs were a magnitude lower than the values for moving sand and moss crusts, which, in turn, were greater than algae crust values. However in dry conditions, the unsaturated hydraulic conductivity (soil water potential <−0.01 MPa) rose as the number of sand-fixed years increased [28,29]. The special hydrological and physical characteristics of BSC improved and promoted the soil microhabitats in desert areas and increased water holding capacity.…”
Section: Influences Of Bsc On Various Hydrological Processesmentioning
confidence: 99%
See 3 more Smart Citations
“…The saturated hydraulic conductivity rate and the unsaturated hydraulic conductivity rate near saturation (soil water potential >−0.01 MPa) of the surface soils covered by BSCs were a magnitude lower than the values for moving sand and moss crusts, which, in turn, were greater than algae crust values. However in dry conditions, the unsaturated hydraulic conductivity (soil water potential <−0.01 MPa) rose as the number of sand-fixed years increased [28,29]. The special hydrological and physical characteristics of BSC improved and promoted the soil microhabitats in desert areas and increased water holding capacity.…”
Section: Influences Of Bsc On Various Hydrological Processesmentioning
confidence: 99%
“…They showed that runoff was greater on leeward slopes and these were covered mainly by algal crusts, whereas drier windward slopes were covered with moss crusts. The results of experiments and simulations undertaken by Li et al [25,33] and Wang et al [29] suggested that the influence of BSCs on rainfall infiltration depended primarily on the intensity of the rainfall, regional rainfall levels, the physical and chemical properties of the soil matrix under the crust and cryptogam composition. This comprehensive assessment resolved an international debate that had been ongoing between scientists.…”
Section: Influences Of Bsc On Various Hydrological Processesmentioning
confidence: 99%
See 2 more Smart Citations
“…The low water content of desert soils limits the number of shrubs and its stabilization. The effects of both rainfall and soil surface characteristics on soil water replenishment in re-vegetated desert ecosystems have been studied by Wang et al (2007Wang et al ( , 2008. However, the effect of stemflow on infiltration patterns associated with the soil moisture replenishment is almost totally unexplored.…”
Section: Introductionmentioning
confidence: 99%